Level of characterization development reached by Santiago badmintonists in decision making - Caurel, Amaya Castillo (International research journal of management, IT and social sciences, 2020)
The act of deciding is considered one of the current research problems of Sports Psychology. It is important to know what athletes think, how they analyze game situations and how they make decisions during vital moments of obtaining a satisfactory sporting result. The decision-making guarantees, then, the rapid adaptation of the athlete to emergent situations of training and competition. Badminton as a sport of high strategy demands in those who practice it, perceptual, decisive and execution skills. From a descriptive study, having as sample six badmintonists from Santiago, it is intended to characterize the level of development reached by the latter in decision making. Techniques such as the memory stimulation interview, coach interviews and the game performance evaluation instrument (GPAI) are used as an observation protocol. The present characterization shows that in training and competition, badmintonists present difficulties in the perceptual-cognitive, decisive and executive indicators of the decision process. They also reveal the technical-methodological limitations of the coach in the development of the said process in his athletes.